Between State and Market: Specific forms and Motives of Inter-Organizational Restructurings (IOR) in the French Nonprofit Field - Garaudel, Pierre; Laurent, Adrien; Schmidt, Géraldine; Eynaud, Philippe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
Literature on Inter-Organizational Restructuring (IOR) among nonprofit organizations (NPOs) is mostly focused on US mergers. Despite the diversity of its IOR practices, the French context remains underresearched. Based on an online survey sent to a wide sample of NPOs, we highlight the existence of innovative IOR practices in France. The paper explores the diverse forms and motives of IOR that French NPOs carry out in a context of increasingly strong constraining forces. Our findings show that market orientation cannot fully explain the diversity of IOR practices and corroborate the centrality of the social and political perspectives in IOR.